Qualidade de vida dos cuidadores informais de idosos com doenças crônicas. - Lima Júnior, Antônio Helton Cavalcante (2023)
Introduction: The growth of the elderly population is a worldwide phenomenon, where unfortunately aging has a low quality of life. This raises a fundamental question about the development of care, the caregiver. The caregiver is a family or non-family person who cares for an elderly person who shows dependence (to a greater or lesser degree). Objectives: Through this, this research sought to emerge the questions about the quality of life of these caregivers, aiming to assess the quality of life of caregivers of bedridden elderly people with chronic diseases, analyzing the relationship, difference and prediction relationship, having as variables the socioeconomic and economic factors (gender, age, education, income, skin color, professional activity, family organization, leisure, sports, religion, etc.) and psychosocial (Burden, Anxiety, Depression, Stress, COPING, Social Support, Spirituality). Methodology: This study is a quantitative, exploratory, correlational and cross-sectional study. Support was obtained from community health agents for the application of the questionnaires. Having an audience of 50 participants, mostly female and having an average age of 52 years. With the approval of the research ethics committee. Result and discussion: In view of the above, the following guiding question was reached: How is the quality of life of caregivers of the elderly in the municipality of Sobral/CE. In response to the questions raised, there was a greater burden and anxiety in participants who did not have support to carry out the activities, caregivers who do not have partners and those who cohabit with the elderly caretaker have a higher incidence of anxiety and a decrease in their quality of life. Conclusion: With this, we can emphasize that the most overloaded informal caregivers are those with more advanced age and who care for a greater number of hours a day, without help to provide care, thus it is noted how difficult and complex these are. factors. It was noted that anxiety, depression and stress have been increasingly strong in this population, which ends up impacting their quality of life process, these caregivers are increasingly overloaded, being strengthened on a daily basis by their religiosity, which ends up being a support and overcoming strategy.